A NEW SPECIES of ISCHNOCNEMA (ANURA) FROM THE SAO FRANCISCO BASIN KARST REGION, BRAZIL - Canedo, Clarissa [UNESP]; Targino, Mariane; Leite, Felipe S. F.; Haddad, Celio Fernando Baptista [UNESP] (Herpetologists League, 2012)
Rio Silo Francisco basin, State of Minas Gerais, Brazil. The new species is diagnosed by the possession of a W-shaped mark on the back, at the level of the shoulder, with one tubercle at each posterior point, red iris in life, and moderate-sized discs on fingers III and IV. These characteristics resemble those of Ischnocnema manezinho and J. sambaqui (from the I. lactea series) but also that from the species in the I. verrucosa series.
Keywords: Amphibia; Anura; Brachycephalidae; Ischnocnema; Taxonomy